Finite Element Analysis of Patient-Specific Condyle Fracture Plates: A Preliminary Study. Issue 2 (June 2015) - Aquilina, Peter; Parr, William C. H.; Chamoli, Uphar; Wroe, Stephen
Various patterns of internal fixation of mandibular condyle fractures have been proposed in the literature. This study investigates the stability of two patient-specific implants (PSIs) for the open reduction and internal fixation of a subcondylar fracture of the mandible. A subcondylar fracture of a mandible was simulated by a series of finite element models. These models contained approximately 1.2 million elements, were heterogeneous in bone material properties, and also modeled the muscles of mastication. Models were run assuming linear elasticity and isotropic material properties for bone. The stability and von Mises stresses of the simulated condylar fracture reduced with each of the PSIs were compared. The most stable of the plate configurations examined was PSI 1, which had comparable mechanical performance to a single 2.0 mm straight four-hole plate.